2020
DOI: 10.1001/jamanetworkopen.2020.28320
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Delay and Pathological Outcomes for Clinically Localized High-Risk Prostate Cancer

Abstract: Key Points Question Is delayed radical prostatectomy for high-risk prostate cancer associated with negative patient outcomes? Findings In this cohort study of 32 184 patients from the US National Cancer Database who underwent radical prostatectomy within 180 days of diagnosis for high-risk prostate cancer, increased surgical delay time was not associated with higher risks of adverse pathological features (pT3-4 disease, node positivity, or positive margin).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
0
15
0
4
Order By: Relevance
“…However, contradictory results regarding the influence of COVID on treatment outcomes in cancer patients were observed. COVID-associated delays would likely not be fatal in patients with breast and prostate cancer, especially during their early stages [ 19 , 20 ]. By contrast, the proportion of lung cancer patients diagnosed with advanced non-small-cell lung cancer was higher during the COVID period [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contradictory results regarding the influence of COVID on treatment outcomes in cancer patients were observed. COVID-associated delays would likely not be fatal in patients with breast and prostate cancer, especially during their early stages [ 19 , 20 ]. By contrast, the proportion of lung cancer patients diagnosed with advanced non-small-cell lung cancer was higher during the COVID period [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer was thought to be exacerbated by the epidemic, more aggressive disease does not indicate a more advanced pathologic stage. Neither COVID nor colorectal cancer stage had a significant effect on pathologic tumor distribution [ 21 , 28 ], nor on pathologic stage in other tumor types [ 19 , 20 ]. The pandemic caused delays in diagnosis or treatment at any disease control stage, and this is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…A delay of 30 days or more has generally found to be associated with worsened BCRFS [10,21,24,34]. However, multiple studies have also found a delay of up to 180 days not to be associated with worsened BCRFS [19,[38][39][40][41]. A delay of 30 days or more is also associated with worsened pathological outcomes [21] in one study.…”
Section: High-risk Patientsmentioning
confidence: 90%
“…A total of 13 studies [10,[18][19][20][21]24,26,29,30,34,[38][39][40][41] reported outcomes of delayed RP compared to immediate RP in high-risk patients. A delay of 30 days or more has generally found to be associated with worsened BCRFS [10,21,24,34].…”
Section: High-risk Patientsmentioning
confidence: 99%
“…So zeigen kleine Nierentumore oft ein geringes Wachstum und ein niedriges Metastasierungsrisiko und für das Prostatakarzinom deuten aktuelle Daten an, dass eine Verzögerung der Behandlung sogar bei hohem Risiko bis zu 6 Monate möglich ist. Der Einzelfall und die psychische Belastung einer Pandemie-bedingten Verzögerung der Therapie eines („Hoch-Risiko-“)Karzinoms bleibt dabei jedoch unbeachtet und sollte nicht unterschätzt werden [ 6 , 10 ]. Dies mag einer der Gründe sein, warum verschiedene urologische Gesellschaften unter anderem auch dem Hoch-Risiko-Prostatakarzinom eine mittlere bis hohe Priorität eingeräumt haben [ 4 , 11 ].…”
Section: Die Auswirkungen Der Coronaviruspandemie Auf Die Urologischeunclassified